Agreement between fragility assessment instruments for older adults registered in primary health care - Beatriz Rodrigues de Souza Melo; Bruna Moretti Luchesi; Gustavo Carrijo Barbosa; Henrique Pott Junior; Tatiana Carvalho Reis Martins; Aline Cristina Martins Gratão (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To assess the level of agreement between the Subjective Frailty Assessment (SFA) and Clinical Functional Vulnerability Index (CFVI-20) for the diagnosis of frailty in older adults. Methods: A descriptive, comparative, cross-sectional study was conducted in 2018/2019 with 492 older adults at nine Family Health Strategy units in the city of Três Lagoas, state of Mato Grosso do Sul, Brazil. Frailty was assessed using the SFA and CFVI-20 in addition to a structured interview. The Wilcoxon test and Pearson's chi-squared test were used for the comparisons. Results: Agreement was 35.4%, with a Kappa coefficient of 0.11. After dichotomizing the sample into frail and non-frail individuals, agreement was 70.1%, with a Kappa coefficient of 0.41 and Cronbach's alpha coefficients of 0.61 and 0.74 for IVCF-20 and SFA, respectively. The prevalence of frailty was lower using the IVCF-20 (17.1%) compared to 59.8% using the SFA. Conclusion: Agreement regarding the classification of frailty between the two instruments ranged from low to moderate. This finding underscores the need for a standardized instrument for measuring frailty in community-dwelling older adults.